Contrasting response of rainfall extremes to increase in surface air and dewpoint temperatures at urban locations in India - Haider Ali (Nature Portfolio, 2017)
Abstract Rainfall extremes are projected to increase under the warming climate. The Clausius-Clapeyron (C-C) relationship provides a physical basis to understand the sensitivity of rainfall extremes in response to warming, however, relationships between rainfall extremes and air temperature over tropical regions remain uncertain. Here, using station based observations and remotely sensed rainfall, we show that at a majority of urban locations, rainfall extremes show a negative scaling relationship against surface air temperature (SAT) in India. The negative relationship between rainfall extremes and SAT in India can be attributed to cooling (SAT) due to the monsoon season rain events in India, suggesting that SAT alone is not a good predictor of rainfall extremes in India. In contrast, a strong (higher than C-C rate) positive relationship between rainfall extremes and dew point (DPT) and tropospheric temperature (T850) is shown for most of the stations, which was previously unexplored. Subsequently, DPT and T850 were used as covariates for non-stationary daily design storms. Higher magnitude design storms were obtained under the assumption of a non-stationary climate. The contrasting relationship between rainfall extremes with SAT and DPT has implications for understanding the changes in rainfall extremes in India under the projected climate.